INTERACTIVE DISCUSSION ON ACCOUNTING AND HUMAN RESOURCE MANAGEMENT WITH SMES AT BANGKOK SHOPPING CENTERS - Wenni Wahyuandari; Lona Chinsia Alfattama (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
Small and Medium Enterprises (SMEs) play a vital role in economic growth and employment, particularly in Southeast Asia. Despite their significance, many SMEs face persistent challenges in  implementing  proper  accounting  practices  and  effective  human  resource  management (HRM), which limit their business sustainability and competitiveness. This community service program aimed to address these challenges through an interactive discussion on accounting and HRM with SMEs operating in shopping centers in Bangkok, Thailand. The activity was conducted from 20–23 February 2025 and involved SME owners and managers as primary participants. Using a participatory and two-way discussion approach, the program introduced practical accounting techniques, such as simple financial recording and cash flow management, as well as basic HRM strategies related to employee motivation, retention, and work efficiency. The results of the activity indicate that most SMEs still rely on informal management practices but demonstrate strong motivation to improve when provided with practical and accessible knowledge. The interactive format facilitated effective knowledge exchange between academics and   entrepreneurs   and   strengthened   cross-cultural   collaboration   between   Indonesian academics   and   Thai   SMEs.   Overall,   the   program   contributed   to   enhancing   SMEs’ understanding of accounting and HRM, supporting their long-term business sustainability, and reinforcing the role of universities in international community engagement and sustainable economic development.